2018
DOI: 10.1377/hlthaff.2017.1321
|View full text |Cite
|
Sign up to set email alerts
|

Four States With Robust Prescription Drug Monitoring Programs Reduced Opioid Dosages

Abstract: State prescription drug monitoring programs (PDMPs) aim to reduce risky controlled-substance prescribing, but early programs had limited impact. Several states implemented robust features in 2012-13, such as mandates that prescribers register with the program and regularly check its registry database. Some states allow prescribers to fulfill the latter requirement by designating delegates to check the registry. The effects of robust PDMP features have not been fully assessed. We used commercial claims data to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 30 publications
2
90
0
Order By: Relevance
“…There is growing consensus that prescribing of opioid analgesics initiated an epidemic of addiction and overdose in the United States . In response, there have been multiple initiatives to limit opioid prescribing , which could reduce the burden of opioid use disorder (OUD) and its associated harms by avoiding initial exposure to prescription opioids among individuals receiving treatment for pain or by promoting safer treatment regimens for those who do start opioid analgesics , thus mitigating OUD and overdose risk. Alternatively, these measures may also limit non‐medical use of prescription opioids if they reduce diversion of opioid analgesic medication …”
Section: Introductionmentioning
confidence: 99%
“…There is growing consensus that prescribing of opioid analgesics initiated an epidemic of addiction and overdose in the United States . In response, there have been multiple initiatives to limit opioid prescribing , which could reduce the burden of opioid use disorder (OUD) and its associated harms by avoiding initial exposure to prescription opioids among individuals receiving treatment for pain or by promoting safer treatment regimens for those who do start opioid analgesics , thus mitigating OUD and overdose risk. Alternatively, these measures may also limit non‐medical use of prescription opioids if they reduce diversion of opioid analgesic medication …”
Section: Introductionmentioning
confidence: 99%
“…Haffajee et al., (2018) is included in two study design categories: interrupted time series with comparison and controlled pre‐post.…”
Section: Resultsmentioning
confidence: 99%
“…Most existing studies evaluating the impacts of PDMPs focused on prescription opioids related outcomes. Although the effects of the implementation of PDMPs or access to PDMP data were mixed, recent studies suggested that the mandatory use of PDMP data was promising in reducing opioid prescribing and related mortality .…”
Section: Introductionmentioning
confidence: 99%